Influence of lactose and lactate on growth and b-galactosidase activity of potential probiotic Propionibacterium acidipropionici - Zarate, Gabriela del Valle (2012)
Dairy propionibacteria are microorganisms of interest for their role as starters in cheese technology and as well as their functions as probiotics. Previous studies have demonstrated that Propionibacterium acidipropionici metabolize lactose by a β-galactosidase that resists the gastrointestinal transit and the manufacture of a Swiss-type cheese, so that could be considered for their inclusion in a probiotic product assigned to intolerant individuals. In the present work we studied the effect of the sequential addition of lactose and lactate as first or second energy sources on the growth and β-galactosidase activity of P. acidipropionici Q4. The highest β-galactosidase activity was observed in a medium containing only lactate whereas higher final biomass was obtained in a medium with lactose. When lactate was used by this strain as a second energy source, a marked increase of the intracellular pyruvate level was observed, followed by lactate consumption and increase of specific β-galactosidase activity whereas lactose consumption became negligible. On the contrary, when lactose was provided as second energy source, lactic acid stopped to be metabolized, a decrease of the intracellular pyruvate concentration was observed and β-galactosidase activity sharply returned to a value that resembled the observed during the growth on lactose alone. Results suggest that the relative concentration of each substrate in the culture medium and the intracellular pyruvate level were decisive for both the choice of the energetic substrate and the β-galactosidase activity in propionibacteria. This information should be useful to decide the most appropriate vehicle to deliver propionibacteria to the host in order to obtain the highest β-galactosidase activity.